Observations of entomophagy across Benin – practices and potentials - Riggi, L.; Veronesi, M.; Goergen, Georg E.; MacFarlane, C.; Verspoor, R.L. (Springer, 2016)
Food security is a critical issue for many low-income countries, particularly in Sub-Saharan Africa. Appropriately identifying and utilising local resources can provide sustainable solutions to food security problems. Insects, which are traditionally consumed in many regions of the world, represent one such resource. Insects can be nutritionally rich and therefore could be used to address issues of malnutrition. A first step towards utilising insects as a resource is identifying which ones are traditionally consumed. We present data collected between 2005 and 2012 on insects eaten by communities across Benin, West Africa. A combination of literature research, field collections, community focus groups and targeted interviews were employed. Data on four ethnic groups is presented: the Anii, Fon, Nagot and Waama. Twenty-nine arthropods species are eaten across Benin. The predominant orders are Orthoptera (48 %) and Coleoptera (41 %). New families of edible arthropods in West Africa include: Bradyporidae (Orthoptera), Coreidae (Hemiptera), Dytiscidae (Coleoptera), Ixodidae (Acari). Insect collection is an ancestral tradition in all the described communities: however, there are considerable differences in preferences and collection methods among ethnic groups. Currently there is little valorisation of insects as a food product in Benin, in contrast to neighbouring countries. In light of considerable malnutrition in Benin among young children, promoting this tradition and implementing small scale captive rearing of selected species could improve food security.